Insomnia With Physiological Hyperarousal Is Associated With Hypertension. Issue 3 (March 2015) - Li, Yun; Vgontzas, Alexandros N.; Fernandez-Mendoza, Julio; Bixler, Edward O.; Sun, Yuanfeng; Zhou, Junying; Ren, Rong; Li, Tao; Tang, Xiangdong
<x xml:space="preserve">Abstract</x> Previous studies have suggested that insomnia with objective short sleep duration is associated with a higher risk of hypertension, and it has been speculated that the underlying mechanism is physiological hyperarousal. In this study, we tested whether insomnia with physiological hyperarousal measured by Multiple Sleep Latency Test (MSLT), a standard test of sleepiness/alertness, is associated with increased risk of hypertension. Two hundred nineteen chronic insomniacs and 96 normal sleepers were included in this study. Chronic insomnia was defined based on standard diagnostic criteria with symptoms lasting ≥6 months. All subjects underwent 1 night in laboratory polysomnography followed by a standard MSLT. We used the median mean MSLT value (ie, >14 minutes) and the 75th percentile of mean MSLT value (ie, >17 minutes) to define hyperarousal. Hypertension was defined based either on blood pressure measures or on diagnosis treatment by a physician. After controlling for age, sex, body mass index, apnea–hypopnea index, diabetes mellitus, smoking, alcohol, and caffeine use, insomnia combined with MSLT >14 minutes increased the odds of hypertension by 300% (odds ratio=3.27; 95% confidence interval=1.20–8.96), whereas insomnia combined with MSLT >17 minutes increased even further the odds of hypertension by 400% (odds ratio=4.33; 95% confidence interval=1.48–12.68) compared with normal sleepers with MSLT ⩽14 minutes. Insomnia associated with physiological hyperarousal is associated with a significant risk of hypertension. Long MSLT values may be a reliable index of the physiological hyperarousal and biological severity of chronic insomnia.